Implications of injury on athlete experiences with positional competition in sport - Davidson, C.; McGuire, C. S.; Profeit, M. C.; Harenberg, S.; Caron, J. G.; Martin, L. J. (Journal of Sport & Exercise Psychology, 2025)
Despite the prevalence of injury and positional competition (PC) in sport, the ways in which injury influences athletes` experiences with PC has yet to be investigated. The purpose of this study was to explore (a) how injury influences athletes` PC experiences and (b) how injury and PC together influence individual- and team-level outcomes. A two-phase qualitative approach was adopted situated within the Canadian interuniversity football context. In Phase 1, 12 athletes participated in semistructured interviews. The findings from these interviews were then discussed in focus group interviews with eight additional athletes (Phase 2). Data were analyzed through a critical realist lens. Three major themes were identified: (a) competing while injured—a perceived unavoidable reality of PC, (b) player status is a key feature of athletes` injury and PC experiences, and (c) a double-edged sword—injury creates and takes away playing time opportunities. Theoretical and practical implications are discussed.